Role ambiguity, person-job fit and job performance among outsourcing employees / Muhamad Khalil Omar and Shamsiah Noor Samsuri - Omar, Muhamad Khalil; Samsuri, Shamsiah Noor (Universiti Teknologi MARA, Perlis, 2017)
The main objective of this study is to examine the relationship of role ambiguity, person-job fit and job performance among outsourcing employees. Past studies indicate that both role ambiguity and person-job fit has significant relationship with job performance. Thus, focus of this study is to discover and to examine whether such relationship exists among outsourcing employees, as their job performance will have direct impact on the employer's contract. There were 200 questionnaires distributed and 183 respondent has participated in the survey. To test the hypotheses, multiple regression technique was employed. The result revealed significant relationship between the respective independent variables and job performance. The hypothesis testing indicates strong positive relationship of person-job fit and job performance but weak negative relationship between role ambiguity and job performance. The findings of this study will offer valuable insights to outsourcing company to strengthen the good HRM practices that will boost up the performance of their employees.